UTILIZATION OF RESOURCES THAT EXIST IN THE NETWORK BY USING ACTIVE DIRECTORY WINDOWS SERVER 2003 - Linda Wahyu Widianti (JAKSTIK Journal, 2006)
Growing computer network systems and the Internet makes every activity and can be done without having to leave my job. This occurs because tersambungnya almost all computers in the world so they can communicate with each other and exchange information.Â  Due to the development tersebutlah, directly participate greatly affect the way we communicate, especially in data communication for computers. If the first one computer to communicate between computers using Workgroup concept, whereas now use the concept of Domain. Where nature is known to centralize Domain Domain is the central database is from an Active Directory.Â  All relevant services and activities exist in Active Directory Domain is. Therefore the use of Active Directory is very meaningful and very easy computer data transfer activities to support various activities based on computer technology.